1996
DOI: 10.2307/1243867
|View full text |Cite
|
Sign up to set email alerts
|

Second‐Best Tax Policies to Reduce Nonpoint Source Pollution

Abstract: Control of nonpoint source pollution often requires regulation of inputs, but first-best solutions are unattainable. Because inputs are monitored by different agencies and regulatory coordination can be costly, it may be more practical to regulate single inputs. A cost-effectiveness approach to determining the best single-input tax policy is developed and applied to the question of reducing nitrate leaching from lettuce production in California. Water is the best single input to regulate, and efficiency losses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
2
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 4 publications
2
50
2
2
Order By: Relevance
“…Cette dernière permet de minimiser le coût global de réduction de la pollution (Pigou, 1932;Tietenberg, 1990;Barde et Smith, 1997). Dans le cas où l'information fait défaut ou est trop onéreuse à obtenir pour l'instance régulatrice, on peut être amené à préférer des schémas indirects de second rang sous-optimaux, mais efficaces du point de vue du coût d'application (Larson et al, 1996).…”
Section: Régulation Des Externalitésunclassified
“…Cette dernière permet de minimiser le coût global de réduction de la pollution (Pigou, 1932;Tietenberg, 1990;Barde et Smith, 1997). Dans le cas où l'information fait défaut ou est trop onéreuse à obtenir pour l'instance régulatrice, on peut être amené à préférer des schémas indirects de second rang sous-optimaux, mais efficaces du point de vue du coût d'application (Larson et al, 1996).…”
Section: Régulation Des Externalitésunclassified
“…Since it generally isn't, an alternative is to impose existing quality requirements on the management problem. 9 In what follows it will be assumed that quality does not affect production. It will be shown that even in this case, the existence of a restriction on Ψ means that optimal policy must again consider stock effects on quantity and quality jointly.…”
Section: Minimum Quality Requirementsmentioning
confidence: 99%
“…The implementation of emissions taxes is even less attractive in the joint quantity/quality dynamic model because water has to be taxed anyway due to the scarcity problem. These two papers, as well as Larson et al [9], deal specifically with the issue of suboptimal input-based instruments, such as uniform taxes for different users or singleinput taxation. Additional inefficiencies of simpler schemes might appear in the dynamic case, since optimal tax levels require continuous adjustment to reflect changing scarcity and quality costs.…”
Section: Minimum Quality Requirementsmentioning
confidence: 99%
See 2 more Smart Citations